The Analysis of Factors Affecting Profitability - Tiffany Tiffany; Sufiyati Sufiyati (Graduate Program of Universitas Tarumanagara, 2023)
Every company would want a good company performance in order to get maximum profit. The purpose of this study was to determine and identify the impact of company size, quick ratio, leverage, asset turnover and asset structure on profitability. The study covers all listed companies listed on the Indonesian Stock Exchange from 2017 to 2020. The testing in this study was carried out using the Eviews version 12 software and by taking samples using a purposive sampling technique with certain criteria. This study used secondary data and used multiple regression analysis to test hypotheses. The results of the study partially show that the firm size and debt to equity ratio variables have no negative effect on profitability. Quick ratio and asset structure have a negative effect on profitability. The asset turnover has no positive effect on profitability.